PENILAIAN KINERJA (PERFORMANCE APPRAISAL) PEGAWAI NEGERI SIPIL DENGAN MENGGUNAKAN KOMBINASI METODE KEY PERFORMANCE INDICATOR DAN 360 DEGREE FEEDBACK - Arisandy, Yosy (Institut Agama Islam Bengkulu, 2017)
Performance appraisal of Civil Servants was conducted with an emphasis on the achievement of target achievement level employee or the work that has been prepared and agreed upon between the Civil Service and the Office of Evaluation. According to Article 4 PP 46 In 2011, the performance appraisal of civil servants divided into two elements Work Target (SKP) and Work Behaviour. However there remain weaknesses in the system of evaluation of the problems which arose at the standard value of the standard to determine the quality of the civil servants and minimum performance assessment conducted only in charge of the assessment by the employer's subjective assessment of opportunities. In management performance assessment can be done by using Key Performance Indicator and 360 degree feedback. With the combination of both the expected performance evaluation of the performance appraisal of civil servants that is more measurable, objective and effective as an input to the Civil Service Agency (BKN).Â Keywords: Performance Evaluation, Target Officers, Civil Servants, Key Performance Indicators, 360 degree feedback